Review of Clinical Validation of ADHD Behavior Rating Scales - Snyder, Steven M.; Hall, James R.; Cornwell, Sonya L.; Quintana, Humberto (Psychological reports, 2006)
The purpose of this review is to assess the range of overall accuracies for Attention Deficit/Hyperactivity Disorder (ADHD) behavior rating scales evaluated in clinical validation studies. Studies were characterized according to the evidence standards of the American Academy of Neurology (AAN). Studies were excluded due to major design problems such as overfitting by discriminant analysis. The 13 included evaluations of rating scales revealed overall accuracy in the range of 59%–79% with a pooled mean of 69% (±7%, standard deviation) and a pooled sample size of 2,228 subjects from nine studies. While some of the excluded studies demonstrated higher overall accuracies (>79%), these studies were observed to have factors in experimental design and statistics that are known to unduly inflate accuracy. We recommend further research following the full AAN standards, namely well-designed, blinded, prospective studies of rating scales applied to clinically representative samples evaluated with a clinical standard.